Effect of a local foot-and-mouth disease vaccine candidate on TNF-α concentration and muscle necrosis in mice - Vengine Ulyama; Fedik Abdul Rantam; Vega Decline; Yulianna Puspitasari; Hani Plumeriastuti; Jola Rahmahani; Mohammad Anam Al Arif (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Foot-and-mouth disease (FMD) is a contagious transboundary disease that causes livestock losses. Vaccination is central to FMD control, but its effectiveness depends on the antigenic relevance to field strains. This study evaluated the safety and immunological response of a local isolate-based inactivated FMD vaccine candidate in mice. Eighty BALB/c mice were divided into four groups: adjuvant-only control, inactivated FMD virus antigen at 10⁸ TCID₅₀, 10⁷ TCID₅₀ with Montanide ISA, and 10⁶ TCID₅₀ with Montanide ISA. Immunization occurred intramuscularly on days 0 and 14. Tumor necrosis factor-alpha (TNF-α) concentrations were measured by ELISA, and injection-site tissues were examined histopathologically for necrosis. TNF-α concentrations increased after immunization, peaking post-booster in the adjuvanted 10⁷ TCID₅₀ group. Histopathology showed preserved architecture with no detectable necrosis. These findings suggest a systemic immune response without local muscle damage. Further studies in livestock are required to confirm protective efficacy, neutralizing antibody responses, and field-level safety.